Genetic characterization and whole-genome sequencing-based genetic analysis of influenza virus in Jining City during 2021–2022 - Li, Libo; Liu, Tiantian; Wang, Qingchuan; Ding, Yi; Jiang, Yajuan; Wu, Zengding; Wang, Xiaoyu; Dou, Huixin; Jia, Yongjian; Jiao, Boyan (Frontiers in Microbiology, 2023)
Influenza virus has a high mutation rate and is a significant threat to global public health. This study collected 1543 throat swab samples from patients with influenzalike illnesses in Jining, northern China during 2021-2022. The nucleic acid detection of influenza A H1N1, seasonal H3N2, B/Victoria, and B/Yamagata strains was performed, and 24 influenza virus strains were whole-genome sequenced and analyzed B/Victoria influenza virus was found to be dominant in Jining during 2021- 2022. The whole genome sequencing results showed that B/Victoria influenza viruses located in the branches of Victoria clade 1A .3a.1 and Victoria clade 1A .3a.2 were coprevalent in Jining in 2021-2022, with high incidence in winter and spring. Compared with the northern hemisphere vaccine strain B/Washington/02/2019, the 8 gene segments of the 24-sequence influenza virus showed lower similarity in HA, MP and PB2. The antigenic epitopes of HA were all mutated at R133G, N150K and N197D, and the 17 sequence antigenic epitopes had more than 4 amino acid variation sites, resulting in antigenic drift. A sequence with a D197N mutation in NA can make NA inhibitor-resistant, but no PA inhibitor resistance mutation. 7 sequences with K338R mutation in PA can enhance the polymerase's replication ability. In summary, this study shows that the influenza B/Victoria strains are mainly prevalent in Jining from 2021 to 2022, and a certain number of amino acid site variations occur in the antigenic epitopes. Furthermore, only a few NA inhibitor-resistant strains have been found, and NA inhibitors and PA inhibitors can still be widely used in the treatment of influenza B